Female director in boardroom: Does it affect board compensation package and firm performance in Saudi Arabia? - Siti Norwahida Shukeri; Faisal D Alfordy (Cogent Business & Management, 2022)
Global gender diversity initiatives driven by international organizations, such as the International Monetary Fund (IMF) and the Organization for Economic Cooperation and Development (OECD) demand more participation of women in corporate boardroom. Nevertheless, prior research relating to the participation of women on corporates' boards provides equivocal conclusions, particularly in the event of strong family ties. This study aims to examine the ownership of female directors on board compensation package and firm performance in Saudi Arabia. Employing a sample of 73 listed Saudi corporations on Tadawul Stock Exchange, the findings reveal only 8.1% of firms in Saudi Arabia have female directors in boardroom and their representation is highly driven by the factor of controlling families concentrated ownership. In addition, the regression analyses show the presence of female directors in Saudi corporate board influences higher board compensation packages, signaling negative impact to these corporations as there is no significant association documented between female directors and financial performance. Being among the first in the MENA region, the study believes the findings provide new insights as it has high level of applicability to other corporate sector in MENA region that sharing similar corporate culture dominated by concentrated ownership structures and male counterparts.
Keywords: 650; Board Compensation Package; Corporate Governance; Family Control; Female Director; Gender Diversity